Beyond T-Cells: Functional Characterization of CTLA-4 Expression in Immune and Non-Immune Cell Types - Oyewole-Said, Damilola; Konduri, Vanaja; Vazquez-Perez, Jonathan; Weldon, Scott A.; Levitt, Jonathan M.; Decker, William K. (Frontiers in Immunology, 2020)
The immune response consists of a finely-tuned program, the activation of which must be coupled with inhibitory mechanisms whenever initiated. This ensures tight control of beneficial anti-pathogen and anti-tumor responses while preserving tissue integrity, promoting tissue repair, and safeguarding against autoimmunity. A cogent example of this binary response is in the mobilization of co-stimulatory and co-inhibitory signaling in regulating the strength and type of a T-cell response. Of particular importance is the costimulatory molecule CD28 which is countered by CTLA-4. While the role of CD28 in the immune response has been thoroughly elucidated, many aspects of CTLA-4 biology remain controversial. The expression of CD28 is largely constrained to constitutive expression in regulatory T-cells (Tregs) as well as inducible expression on activated conventional T-cells (Tconv) and as such, teasing out its function has been somewhat simplified by its limited and specific expression profile. The expression of CTLA-4, on the other hand, has been reported on a highly diverse repertoire of cells within both lymphoid and myeloid lineages as well as on the surface of tumors. Nonetheless, despite a widespread expression pattern, the function of CTLA-4 has been mostly described within the context of T-cell biology. The focus on T-cell biology may be a direct result of the high degree of amino acid sequence homology between CD28 and CTLA-4, especially in light of their co-expression on activated Tconv and Treg. Furthermore, observations of the outsized role of CTLA-4 in Treg-mediated immune suppression and the striking phenotype of T cell hyperproliferation and resultant disease in CTLA-4-/- mice contribute to T-cell bias in the study of CTLA-4. Complete elucidation of CTLA-4 biology will require a more nuanced understanding of its role in a context other than that of T-cells. This makes particular sense in light of the remarkable, yet limited utility of anti-CTLA-4 antibodies in the treatment of cancers and of CTLA-4-Ig in autoimmune disorders like rheumatoid arthritis. By fully deducing the biology of CTLA-4-regulated immune homeostasis, bottlenecks that hinder the widespread applicability of CTLA-4-based immunotherapies can be resolved.